Diversity of fern species in different ecosystem types :case study at Gunung Jagoi, Bau, Sarawak, Malaysia - Siti Nurlatifah, Binti Salehhudin (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study using plot sampling method to determine the diversity and distribution of fern species in two different forest types: kerangas forest and mixed dipterocarp forest (MDF) in Gunung Jagoi have been carried out. In kerangas forest, a total of 2,251 individuals belonging to nine different families and in MDF, a total of 2,844 individuals belonging to 13 different families have been recorded. Analysis on the importance values (Iv) of fern species was enumerated and quantified the dominant and the least dominant species. In kerangas forest, the dominant fern species is Selaginella canaliculata and least dominant species is Metathelypteris flaccida. Whereas in MDF, the dominant species is Coniogramme fraxinea and least dominant species is Sphaerostephanos porphyricola. The distribution of fern species also has been identified based on the relative frequency for all established plots in different elevation.